Terminologie Numérique : Conception, Représentation et Gestion. - Vezzani, Federica (Bern : Peter Lang AG International Academic Publishers, 2022)
This book focuses on digital terminology and illustrates the design and implementation of multilingual terminological databases. Through the formulation of the FAIR terminology paradigm we provide guidelines for the optimal representation of these resources in accordance with ISO standards for terminology management.
5.5 Répertoire des catégories de TriMED -- 5.6 Mise en œuvre TBX -- 5.6.1 Formulation du dialecte TBX-TriMED -- 5.6.2 Position des catégories de données -- 5.7 Application Web TriMED -- 5.7.1 Utilisateurs -- 5.7.1.1 Le patient -- 5.7.1.2 Le traducteur -- 5.7.1.3 Le médecin -- 5.8 Application Web RCD -- 5.9 Collection terminologique -- 5.10 Conclusion -- 6 Is it FAIR enough? -- 6.1 Resource Description Framework - RDF -- 6.2 De TBX à RDF -- 6.3 Conclusion -- Annexe A -- Annexe B -- Bibliographie -- Index -- Titres de la collection.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books